Companions' Interventions on Behalf of Patients - Johanna Ruusuvuori; Charles Antaki; Deborah Chinn (Social Interaction)
Some patients require a companion to help them answer questions from medical personnel. How the companions do so may depend, in part, on the nature of the patient’s condition. In the case of the patient with a learning disability, we find the companion tending strongly to respect the patient’s agency and entitlement to speak to their own experiences, by a) allowing the patient time to volunteer the answer to the question themselves, b) glossing inadequate answers as being a temporary failure to remember and c) constructing a no-problem answer (extending previous findings by Antaki and Chinn, 2019). In contrast, with a patient who is examined for or has a diagnosis of epilepsy or multiple sclerosis, we see the companion tending to take a more proactive and interventionist approach. We discuss our findings in the light of differences between the powers and capacities attributable to people with learning disability, epilepsy, and multiple sclerosis, and the different entitlements that their companions may assume in speaking for them.